(untitled) - Gault, Victor A. (Chichester, West Sussex, 2009)
In this textbook the authors have covered basic principles, terminology and core technologies, which include key modern experimental techniques and equipment used to analyse important biomolecules in diagnostic, industrial and research settings.
Keywords: Analytical biochemistry,Biochemistry,Molecular biology